Federalism vs. Federalismo: not all the roads lead to Rome. DOI 10.5935/2448-0517.20180007 - Duarte, Fernanda; Iorio Filho, Rafael Mario (Juris Poiesis - Qualis A3, 2018)
This paper is part of our research project that has been going on for a couple of years in our research group called "Center for Legal Studies, Citizenship, Procedure and Discourse", located at Estácio de Sá University, Rio de Janeiro, Brazil. In order to illuminate the idea that legal systems cannot be translated/verted straightforwardly as if they were a mere lexicon translation challenge, we apply the semiolinguistic methodology of discourse analysis and the method of comparison by difference (this latter borrowed from Antropology) to provide a description for native and/or theoretical categories of the Brazilian legal culture in contrast with American legal culture. We agree that there is much more about it that relates to meaning and understanding surpassing the linguistic problem. From the theoretical point of view our observations may be arranged in three sets of ideas: a) the understanding of Law as a set of local discourses and practicesí¾ b) the utility of the theoretical category "legal sensibilities" (GEERTZ ,1983)í¾ c) the recognition that culture interferes in socialization and social efficacy of Law when people translate legal categories. It is broadly said in Brazil that literal translations between legal concepts and categories of different legal systems are not only possible and but also feasible. For instance "judicial review" (controle de constitucionalidade in Portuguese) would be the same in American and Brazilian law, as if the words would only need a proper and accurate translation exercise to convey their proper meaning. However to show that this correspondence is tricky and dangerous we have been selecting different categories and putting them into description and analysis in the Brazilian and American legal cultures. Previously we have dealt with two other categories: equal protection vs. igualdade juridica and due process of law vs. devido processo legal. This turn we have picked the category of federalism (federalismo in Portuguese). We believe this approach can work as a vaccine against uncritical transplantations of legal categories that ultimately become out of place with low capacity to interfere with reality and to shape behaviors that involve the enforcement of law.